2016
DOI: 10.1007/s10926-016-9659-9
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ Perceptions of Social Norms as a Result of Implementing the Participatory Approach at Supervisor Level: Results of a Randomized Controlled Trial

Abstract: Purpose A multifaceted implementation strategy was targeted at supervisors to encourage them to apply a participatory approach (PA) in dealing with employees’ work functioning problems due to health concerns. This paper assesses the effect on employees’ perceived social norms regarding the use of the PA to deal with work functioning problems. Methods Three organizations participated in a cluster randomized controlled trial, with randomization at the department level. Supervisors in the PA intervention departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Cultural and social norms are expected to differ across societies and careers (Ketelaar et al, 2016). According to the study by Hudek, Tominc, and Sirec (2021), cultural and social norms are important factors for online freelancers in Slovenia concerning their work.…”
Section: Composite Mean 255 Highmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural and social norms are expected to differ across societies and careers (Ketelaar et al, 2016). According to the study by Hudek, Tominc, and Sirec (2021), cultural and social norms are important factors for online freelancers in Slovenia concerning their work.…”
Section: Composite Mean 255 Highmentioning
confidence: 99%
“…Entrepreneurs in Pakistan perceive that social norms influence their work and they believe that social acceptance can help their businesses rise above others (Ketelaar et al, 2016). Moreover, Verdugo (2021) agrees that social norms affect a country's economic development.…”
Section: Composite Mean 255 Highmentioning
confidence: 99%
“…To date, there is a small body of research suggesting that workplace interventions for managers can improve their knowledge, attitudes, and self-reported behavior in supporting employees experiencing mental health problems (16), and that such training can lead to an increase in the frequency of help-seeking behaviors and mental health resource use amongst employees (17,18). However, the precise content and duration of the interventions in these trials has varied substantially, some trials have reported mixed findings for specific manager (19,20) or employee (21) outcomes, and most trials have focused on face-to-face training. In contrast, the development and adoption of digital training is increasing (22).…”
Section: Introductionmentioning
confidence: 99%